(untitled) (Nexo Revista Científica, 2020)
This work aimed to measure the effect of eugenol on the shelf life of a hot sauce from jalapeño pepper (Capsicum annuum) and papaya (Carica papaya). Cloves were tested as test material, using different forms of eugenol extraction as essential oil. Its use as a preservative in a sauce was evaluated by means of accelerated methods for 30 days at a temperature of 280 C ± 20 C and was compared with sodium benzoate (control) according to the Codex Alimentarius regulations (250 mg / kg). The results determined that eugenol had an inhibitory effect on the change in hot sauce, prolonged its shelf life, indicating its potential application in the food industry, making it a natural preservation alternative, the use of which will help to decrease the toxicological risks provided by synthetic preservatives.